Meningkatkan Keaktifan dan Hasil Belajar Siswa Pada Pembelajaran IPS Melalui Metode Tutor Sebaya - Raudhatul Jannah; Uswatun Nisa; Syaharuddin Syaharuddin (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2023)
The level of student engagement in the classroom has a significant impact on their learning outcomes. Various models and methods employed to enhance student engagement can influence these outcomes. This study aims to investigate the effects of applying the peer tutor method on student engagement and learning outcomes in Class VIII F at SMP Negeri 27 Banjarmasin. The research follows a four-stage process: planning, implementation, observation, and reflection. Data were collected through observation sheets and student engagement records. The results of the study reveal that the implementation of the peer tutor method has a positive impact on student engagement and learning outcomes in Class VIII F at SMP Negeri 27 Banjarmasin. This improvement is evident through the percentages obtained in both Cycle I and Cycle II: Student engagement increased from 34% in Cycle I to 84% in Cycle II. Student learning outcomes improved from 52% in Cycle I to 96% in Cycle II.